Outcome of nursing intervention on knowledge and use of nursing process among nurses in zonal hospitals, rivers state, Nigeria - Ali, Emordi Nnenna (International Journal of Research in Medical Sciences, 2020)
Background: Nursing process if properly utilized help nurses to be accountable and responsible for the care given. With all of its benefits it has suffered poor implementation and utilization in developing countries, Nigeria inclusive. Hence, this study determined the outcome of nursing intervention on knowledge and use of nursing process among nurses in Zonal Hospitals in Rivers State. Methods: This study adopted a two group pretest-posttest quasi-experimental design. Purposive sampling technique was used to select 41 nurse participants who were working in in-patient management units from the 2 Zonal Hospitals. The instrument for data collection included a checklist and nursing process questionnaire. The reliability was determined with a Cronbach’s alpha index range of 0.77-0.91. Descriptive statistics of percentages, mean and standard deviation was used to answer six research questions. Results: The pre-intervention knowledge mean score of nursing process was below average for the two groups but became high in the experimental group at post-intervention. Also, pre-intervention use mean score of nursing process was below average in both groups but high after intervention in the experimental group. Conclusions: The study concluded that nursing intervention was effective in improving the knowledge and use of nursing process among the nurses. Thus, the outcome was positive as changes were noted. It is recommended that in-service educational program should be established to provide continuous education for nurses to refresh their knowledge and enhance their usage of nursing process.